4D Cell Biology: Adaptive optics lattice light-sheet imaging and AI powered big data processing of live stem cell-derived organoids - Schoeneberg, Johannes (J Biomol Tech, 2020)
New methods in stem cell 3D organoid tissue culture, advanced imaging, and big data image analytics now allow tissue-scale 4D cell biology but currently available analytical pipelines are inadequate for handing and analyzing the resulting gigabytes and terabytes of high-content imaging data. We expressed fluorescent protein fusions of clathrin and dynamin2 at endogenous levels in genome- edited human embryonic stem cells, which were differentiated into intestinal epithelial organoids. Lattice light-sheet imaging with adaptive optics (AO-LLSM) allowed us to image large volumes of these organoids (70 × 60 × 40 μm xyz) at 5.7 s/frame. We developed an open-source data analysis package termed pyLattice to process the resulting large (∼60 Gb) movie data sets and to track clathrin-mediated endocytosis (CME) events. We then expressed fluorescent protein fusions of actin and tubulin in genome-edited induced human pluripotent stem cells, which were differentiated into human cortical organoids. Using the AO-LLSM mode on the new MOSAIC (Multimodal Optical Scope with Adaptive Imaging Correction) allowed us to image neuronal migration deep in the organoid. We augmented pyLattice with a deep learning module and used it to process the brain organoid data.